2004
DOI: 10.1090/s0002-9939-04-07279-x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudocompact spaces $X$ and $df$-spaces $C_{c}\left ( X\right ) $

Abstract: Abstract. Let X be a completely regular Hausdorff space, and let Cc (X) be the space C (X) of continuous real-valued functions on X endowed with the compact-open topology. We find various equivalent conditions for Cc (X) to be a df -space, resolving an old question of Jarchow and consolidating work by Jarchow, Mazon, McCoy and Todd. Included are analytic characterizations of pseudocompactness and an example that shows that, for Cc (X), Grothendieck's DF -spaces do not coincide with Jarchow's df -spaces. Any su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Precisely when X is Warner bounded, C c (X) β is a normed space which (we show) contains 1 complemented; C c (X) β is a Banach space precisely when C c (X) is a d fspace [8]. Therefore precisely when X is Warner bounded and not compact, C c (X) is not normable (so ( * ) and ADK do not apply) and yet C c (X) β is a normed space which, by Section 3, has a separable quotient 1 , as does the completion.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Precisely when X is Warner bounded, C c (X) β is a normed space which (we show) contains 1 complemented; C c (X) β is a Banach space precisely when C c (X) is a d fspace [8]. Therefore precisely when X is Warner bounded and not compact, C c (X) is not normable (so ( * ) and ADK do not apply) and yet C c (X) β is a normed space which, by Section 3, has a separable quotient 1 , as does the completion.…”
Section: Introductionmentioning
confidence: 75%
“…Indeed, (9) ⇒ (10) is immediate. We easily argue that ¬(8) ⇒ ¬(10): if M is a closed ℵ 0 -codimensional subspace of a primitive C c (X) σ , then M ⊥ is a copy of ω in C c (X), so X is not pseudocompact [8].…”
Section: Barrelled Spaces With Separable Quotientsmentioning
confidence: 99%
See 1 more Smart Citation
“…admits (ε n ) n ⊂ (0, 1] such that (ε n u n ) n is bounded in E. We prove the converse for E = C c (X) σ ; for arbitrary E we do not know the answer. In [8] and [9] we showed that the bounding cardinal b (see [12]) is the largest cardinal such that the product space R κ is docile when κ < b, and gave proof for the following. Theorem 1.1.…”
Section: Introductionmentioning
confidence: 99%
“…An LCS E is docile [6][7][8][9] if every infinite-dimensional subspace of E contains an infinite-dimensional bounded set. This is weaker than the Fréchet-Urysohn property [6,Theorem 4.1], itself weaker than metrizability.…”
Section: Introductionmentioning
confidence: 99%